2019
DOI: 10.1021/acs.inorgchem.9b01273
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Doping and Site-Sensitive Photoluminescence of Eu3+ and Tb3+ in Perovskite-Type LaLuO3

Abstract: Eu 3+ and Tb 3+ ions were site-selectively doped into LaLuO 3 with the orthorhombic perovskite-type structure (ABO 3 ), and their luminescence properties were examined considering the doping sites (A or B sites). The X-ray diffraction analysis revealed the expansion or contraction of the unit cell volumes of the materials depending on the doping sites. The spectra of X-ray absorption near edge structure for the Eu and Tb L III edge exhibited different shapes for the ions at A and B sites, confirming the site-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 55 publications
7
37
0
Order By: Relevance
“…excitation peaks in the range from 220 to 250 nm. [5][6][7][25][26][27][28][29] The crystal site of Tb 3+ in this assignment is consistent with the results obtained by XRD and XANES measurements. In the PL spectra measured under UV excitation at 247 nm, the Tb 3+ luminescence is composed with two series of transitions from 5 D 3 to 7 F J (J = 6, 5, 4, 3) and from 5 D 4 to 7 F J states.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…excitation peaks in the range from 220 to 250 nm. [5][6][7][25][26][27][28][29] The crystal site of Tb 3+ in this assignment is consistent with the results obtained by XRD and XANES measurements. In the PL spectra measured under UV excitation at 247 nm, the Tb 3+ luminescence is composed with two series of transitions from 5 D 3 to 7 F J (J = 6, 5, 4, 3) and from 5 D 4 to 7 F J states.…”
Section: Resultssupporting
confidence: 90%
“…19,20 The peak shapes provide the information not only on the valence states of Tb ions but also on the occupied crystal sites. 7,21,22 TbAlO 3 shows a main single peak at 7516 eV and two additional broad peaks at 7528 and 7548 eV, while Ba 2 TbTaO 6 exhibits a main peak at 7517 eV with a shoulder at 7514 eV and two broad peaks at 7533 and 7555 eV. The appearance of the shoulder indicates the splitting of the main peak derived from Tb 5d orbitals in Ba 2 TbTaO 6 .…”
Section: Resultsmentioning
confidence: 97%
“…4(d), all peaks were indexed by cubic crystal with parameters close to those of previously reported K 3 YF 6 compound, and the structural parameters of 2 and 3. 43,44 Based on the site occupation fraction in Rietveld renement, the Er 3+ ions sites, the Er2 3+ ions take up $3.6% Sc2/Lu2 sites and Yb2 3+ ions take up $20.3% Sc2/Lu2 sites. 45,46 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of cell volume likely results in the diminishing grain size. In many oxide systems, like TiO 2 , CuO, NaTaO 3 , BaTiO 3 , and ZnWO 4 , it was reported that both surface modification and substitution also play critical roles in modulating the crystalline structure and morphology size. Typically, it is structural relaxation or contraction and atomic anisotropy that results in lattice variation. The phenomenon is matched well with experimental data and is consistent with the previous report.…”
Section: Resultsmentioning
confidence: 99%